Epidemic history of hepatitis C virus genotypes and subtypes in Portugal - C., Palladino, (2018)
Any successful strategy to prevent and control HCV infection requires an understanding of the epidemic behaviour among the different genotypes. Here, we performed the first characterization of the epidemic history and transmission dynamics of HCV subtypes in Portugal. Direct sequencing of NS5B was performed on 230 direct-acting antiviral drugs (DAA)-treatment naïve patients in Lisbon. Phylogenetic analysis was used for subtyping and transmission cluster identification. Bayesian methods were used to reconstruct the epidemic history of HCV subtypes. Sequences were analysed for resistance-associated substitutions (RAS). The majority of strains were HCV-GT1 (62.6%), GT3 (18.3%, all subtype 3a) and GT4 (16.1%). Among GT1, the most frequent were subtypes 1a (75.5%) and 1b (24.5%). Polyphyletic patterns were found in all but 12 lineages suggesting multiple introductions of the different subtypes in this population. Five distinct epidemics were identified. The first significant HCV epidemic in Portugal occurred between 1930s and 1960s, was caused almost exclusively by GT1b and was likely associated with blood transfusions. Rapid expansion of GT3a occurred in the 1960s and GT1a in the 1980s, associated with intravenous drug use. The most recent epidemics were caused by GT4a and GT4d and seem to be associated with the resurgence of opioid use. The C316N substitution was found in 31.4% of GT1b-patients. Close surveillance of patients bearing this mutation and undergoing dasabuvir-based regimens will be important to determine its impact on treatment outcome.